RESISTENSI TERHADAP TRANSFORMASI PENDIDIKAN ISLAM PESANTREN: ANALISIS MOTIF, AKTOR, MODEL DAN STRATEGI PENGENDALIAN - Ahmad Junaidi; Asrop Safi’i Asrop Safi’i; Binti Maunah Binti Maunah (As-Sulthan Journal of Education, 2026)
Resistance to change is a cognitive, emotional and behavioral responses of individuals and groups to process of change. This resistance can appear in closed, semi-open, or open forms, and is manifested individually or collectively according to underlying social context. Influencing factors include structural inertia, group inertia, economics, the impact of change and other related factors. This research is a qualitative descriptive study with a case study design, where data was collected through observation, in-depth interviews and documentation. The data analysis techniques used were Miles and Huberman, consisting of data condensation, data presentation and drawing conclusions. The results concluded that resistance at Cendekia Miftahul Ulum Albajra Islamic Boarding School is individual resistance carried out by individuals who influence social groups with economic motives and group inertia. The Islamic boarding school leader has three strategies to overcome this: a persuasive approach, intensive communication, and negotiation.